Rethinking Nature Relations Beyond Binaries - Keskitalo, E. C. H. (Edward Elgar Publishing, 2023)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This incisive book explores the implications of the nature-culture binary and how it impacts the ways in which we think about nature. Bringing together and building on extensive work from varied fields, E. C. H. Keskitalo maps the many understandings of nature across diverse traditions and histories, and demonstrates that nature relations must be understood in connection to power.